What triangle? There’s no triangle there.
F(x)=2x+4/3
Replace f(x) by y:
y=2x+4/3
Solving for x:
y-4/3=2x+4/3-4/3
Subtracting the two terms on the left side of the equation:
(3y-4)/3=2x
Dividing both sides of the equation by 2:
[(3y-4)/3]/2=2x/2
[(3y-4)/3]*(1/2)=x
[(3y-4)*1]/[(3)*(2)]=x
(3y-4)/6=x
x=(3y-4)/6
Replace "x" by "f^(-1) (x)" (inverse function) and "y" by "x":
f^(-1) (x) = (3x-4)/6 Inverse function
Then, for x=6
f^(-1) (6) = [ 3(6)-4]/6
f^(-1) (6) = (18-4)/6
f^(-1) (6)= 14/6
f^(-1) (6) = 7/3
Her hair will have grown 6 after 7/3 = 2.33 months
Answer:
depends on what the price of the bicycle is and the discount percentage
You sure that’s the radius and not diameter? But if it is, the volume would be 70,276.2 cm
Answer:
Slope is rise over run
Step-by-step explanation:
How many do you go up over how many you go over.